Strategies for increasing the adaptive capacity of the community in vulnerable settlement areas impacted by the mudflow disaster - Ekawati, June; Pangi, Pangi; Hardiman, Gagoek; Pandelaki, Edward E. (International Journal of Disaster Management, 2025)
The mudflow disaster has made the surrounding community's residential areas vulnerable, so efforts are needed to strengthen the communitys adaptive capacity to reduce vulnerability. This study aims to develop strategies to minimize settlements vulnerability based on communities adaptive capacity in areas impacted by the Lapindo mudflow disaster in Sidoarjo, Indonesia. The research method used is the explanatory sequential mixed methods approach with quantitative primary data obtained from structured questionnaires and qualitative data from field surveys and interviews, with analysis in the form of integrating the two databases. The research results showed that the level of community adaptive capacity was moderate, slightly above the average score (3.19). The lowest score was on education level (1.78), and the highest score was on social relations (4,36). The strategies to reduce vulnerability are increasing public education, empowering the community's economy, increasing the availability and capacity of disaster infrastructure, conducting massive reforestation, providing technical assistance, access to banking facilities, clean water networks and distillation, and supporting community activities in social, cultural, and religious fields, as well as strengthening village institutions. This study concludes that social, cultural, and religious variables play a role and become important capital in increasing the community's adaptive capacity, which can later reduce vulnerability in an area towards a disaster-resilient area.